Consent for biobanking: The legal frameworks of countries in the BioSHaRE-EU project. - Kaye, J; Briceño Moraia, L; Curren, L; Bell, J; Mitchell, C; Soini, S; Hoppe, N; Øien, M; Rial-Sebbag, E (Mary Ann Liebert, Inc, 2016)
Currently, there is no single, Europe-wide regulation of biomedical research using human samples and data. Instead, the law that applies spans a number of areas of law, such as data protection, clinical trials, and tissue regulation. In the absence of harmonized regulation, there is considerable scope for national legal variation. This article analyzes the legislative frameworks that apply to biobanking activities to identify differences in legal requirements between the BioSHaRE-EU project countries: Finland, France, Germany, the Netherlands, Norway, and the United Kingdom. This article highlights the primary role of consent and accompanying governance mechanisms, such as research ethics committee oversight, which enable consent exemptions in the context of research. Our analysis identifies a complicated legal landscape, whereby broadly similar provisions are contained in varied sources of law in each jurisdiction. The challenge for researchers is locating the applicable legal provisions within each national legal framework.